Tingkat Penggunaan Ruang Terbuka di Kawasan Permukiman Padat Studi Kasus Kelurahan Pattingalloang dan Kelurahan Gusung Kota Makassar - Rumata, Nini Apriani; Amal, Citra Amalia; Amin, Siti Fuadillah A (Nature: National Academic Journal of Architecture, 2024)
The dense area in Pattingalloang Village and Gusung Village is one of the settlements in Makassar City which has a very high-density level. The condition of the area that is very dense with buildings causes open space that functions as a space for social interaction in this area to be very narrow and even tends to be absent. The limited public space in this research location then has the potential to form a spontaneous public space so that the location of the open space is not by its function, for example, the use of roads as public space so that conflicts arise between spaces. The purpose of this research is to identify open space problems in the Pattingalloang and Gusung Urban Village Solid Settlement Areas and analyze the factors that form open space in the Pattingalloang and Gusung Urban Village Solid Settlement Areas. This research is descriptive research with a qualitative and spatial approach. The data collection technique used is field observation and conducting unstructured interviews. This data collection is based on Behavior Setting which is reviewed from various activities at the research location. The results of this study state that the problem of open space in the study area is territorial change, private space becomes public space and public space becomes private space. Factors that influence and shape the formation of open space